Uso de nanobastões de ouro para o desenvolvimento de aulas práticas de nanotecnologia. - Ferreira, Cyntia Silva (2017)
Use of gold nanoparticles functionalization experiment was conducted in a biotechnology summer course at UFOP as a model for the introduction of the laboratory practice in nanotechnology for postgraduate courses in the areas of chemistry and biotechnology. The gold nanorods were synthesized by the seed method and then, functionalized with anti-IL-6 antibodies using the reagents EDAC/NHS and polyethyleneimine (PEI). This nanocompound was tested against the binding with the specific antigen (IL-6) and changes in the longitudinal plasmon absorption spectrum showed the coupling efficiency, which was also verified by the decrease in zeta potential. The experiment was satisfactory, with a positive feedback from participants, and could be implemented in nanotechnology practical classes from postgraduate courses, as a way for improve education in the emergent area of nanobiotechnology.